An overview of emerging trends in pathogen reduction in the processing of fruit juices - Campbell, Ian Gavin A. (Kansas State University, 2014)
Unpasteurized fruit juices have been implicated as the source of foodborne outbreaks due to pathogens such as Salmonella, Escherichia coli O157: H7 and Cryptosporidium parvum. The growth of pathogens can usually be slowed through freezing or largely eliminated through pasteurization. Although pasteurization is often effective in eliminating pathogens, it often yields undesirable flavors that are unlike those of fresh juice. Growing consumer trends towards “healthy” unpasteurized alternatives are fueling the development of alternative processing techniques. Several promising techniques for pathogen reduction in the processing of fruit juices are currently being developed. A new technique that is already being marketed worldwide is hyperbaric processing (HPP) which subjects the fruit juice to a high pressure of up to 1000 MPa. The high-pressure treatment results in up to a 7 log reduction kill in pathogens while preserving the naturally occurring flavor profile, sensory attributes and nutritional benefits. Pulsed electric fields (PEF) and ionizing radiation are also being widely explored as viable techniques to process unpasteurized fruit juices. PEF promises to be a commercially viable energy efficient alternative to pasteurization, adding only $0.03 – $0.05 per liter to final food costs. Although irradiation enjoys support for use in the processing of fruit juice by regulatory agencies, support in public opinion is lacking and hinders its growth as an alternative to pasteurization. Other experimental techniques are also present in the development pipeline. Ultrasonic radiation and high intensity pulsed light radiation are both experimental techniques that are being researched. A particularly exciting alternative is the use of plant-based antimicrobials. Several fruits and spices are known to be natural antimicrobials and are therefore being researched as alternatives to the traditional chemical preservatives.
Keywords: Pathogen reduction; Fruit juice processing; Food Science (0359)